2018
DOI: 10.1097/bpb.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Gain of length–loss of strength? Alteration in muscle strength after femoral leg lengthening in young patients: a prospective longitudinal observational study

Abstract: This study aimed to determine the alteration in maximum isokinetic torque in patients after intramedullary femoral leg lengthening. Thirty patients with a median leg-length discrepancy of 3.0 cm underwent femoral limb lengthening with an intramedullary motorized device. Maximum isokinetic, concentric torque of the extensors, and flexors of the knee was measured before (n=30) and 2 years after surgery (n=21). Postoperatively, a significant difference remained for the maximum isokinetic torque of the extensors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…On one hand, we cannot rule out that the difference between the limbs was already present before the lengthening procedure as we do not have preoperative measurements. Preexisting differences have previously been described by Krieg et al (2018), who found that the shorter limb was weaker than the longer both before and 2 years after femoral lengthening. On the other hand, the patients in the study by Krieg et al (2018) could have had etiologies associated with impaired physical function of the lengthened limb, a weakness accounted for by the strict inclusion criteria in our study.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…On one hand, we cannot rule out that the difference between the limbs was already present before the lengthening procedure as we do not have preoperative measurements. Preexisting differences have previously been described by Krieg et al (2018), who found that the shorter limb was weaker than the longer both before and 2 years after femoral lengthening. On the other hand, the patients in the study by Krieg et al (2018) could have had etiologies associated with impaired physical function of the lengthened limb, a weakness accounted for by the strict inclusion criteria in our study.…”
Section: Discussionmentioning
confidence: 57%
“…Even though the results are not unambiguous, 2 of 4 hop tests showed a statistically significant difference between the limbs and half of the patients had impaired physical function of the lengthened compared with the unlengthened limb at assessment. Our results are important as the literature is inconsistent in whether femoral lengthening impacts physical function of the lengthened limb or not (Bhave et al 2017, Krieg et al 2018). On one hand, we cannot rule out that the difference between the limbs was already present before the lengthening procedure as we do not have preoperative measurements.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations